The Oxford Handbook of Criminology - Edited by Liebling, Alison ; Maruna, Shadd and McAra, Lesley (United Kingdom Oxford University Press, 2012)
The Oxford Handbook of Criminology provides an authoritative collection of chapters covering the core and emerging topics studied on criminology courses. With contributions from leading academics, the Handbook is the definitive guide to the discipline.
Include Index
Keywords: Criminology